Management Strategy For UMKM Palm Sugar Smes Towards Increasing Competitivenees Through E-Commerce From An Islamic Perspective - Dikri Abdal Haq; Fenny Damayanti Rusmana; Ridla Mutiah (Lafadz Jaya Publisher, 2024)
Cimenteng palm sugar from Cimenteng Village, Cijambe District, Subang Regency, West Java, is known for its high quality thanks to its distinctive sweet taste and soft texture. Since ancient times, palm trees have grown abundantly in this area, and local people have processed the sap into palm sugar. Initially, production was carried out traditionally, but with technological developments, processing using modern equipment has increased efficiency. The advantages of Cimenteng Palm Sugar include its distinctive sweet taste, soft texture, bright color, long shelf life and high nutritional content. Palm sugar plays an important role in the economy of Cimenteng Village, making a major contribution to income and employment. This research discusses strategies for managing palm sugar MSMEs through e-commerce in Cimenteng Village. Survey and interview results show that a lack of understanding of marketing strategies and minimal sales through e-commerce are the main problems for palm sugar MSME entrepreneurs in this village. Management strategies are designed to increase the competitiveness of palm sugar MSMEs, including improving product quality, market access through e commerce platforms, and increasing knowledge about e-commerce. Supporting factors for the strategy involve government support, technological advances, public awareness, and Islamic values. However, limited skills, access to capital, market competition and consumer confidence are inhibiting factors. The conclusion highlights the potential for developing palm sugar MSMEs through an e-commerce strategy that takes Islamic values into account. Recommendations were submitted to the government to provide further support, while palm sugar MSMEs were encouraged to improve product quality, utilize e commerce, and build consumer trust by implementing Islamic values. The community is expected to support the development of palm sugar MSMEs through awareness of the importance of e-commerce.